2020
DOI: 10.3389/fbioe.2020.00056
|View full text |Cite
|
Sign up to set email alerts
|

Biomaterials-Induced Stem Cells Specific Differentiation Into Intervertebral Disc Lineage Cells

Abstract: Stem cell therapy, which promotes stem cells differentiation toward specialized cell types, increases the resident population and production of extracellular matrix, and can be used to achieve intervertebral disc (IVD) repair, has drawn great attention for the development of IVD-regenerating materials. Many materials that have been reported in IVD repair have the ability to promote stem cells differentiation. However, due to the limitations of mechanical properties, immunogenicity and uncontrollable deviations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 129 publications
0
9
0
Order By: Relevance
“…To overcome obstacles for successful disc repair, the selection of appropriate stem cells and the development of biomaterial-based cellular delivery systems that combine cells with cell-carrying matrix molecules such as fibrin and hyaluronan have become increasingly implemented [ 3 ]. Recently, various types of biomaterials have been reported to have the ability to prevent cell leakage and promote cell survival and stem cell differentiation toward the IVD cell phenotype [ 39 ]. Reports demonstrated that utilization of a carrier such as hyaluronan or annular sealant significantly prevented cell leakage, and the rate of osteophyte formation resulting from cell leakage has been reported to be less than 2.7% in rabbit IVD model [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…To overcome obstacles for successful disc repair, the selection of appropriate stem cells and the development of biomaterial-based cellular delivery systems that combine cells with cell-carrying matrix molecules such as fibrin and hyaluronan have become increasingly implemented [ 3 ]. Recently, various types of biomaterials have been reported to have the ability to prevent cell leakage and promote cell survival and stem cell differentiation toward the IVD cell phenotype [ 39 ]. Reports demonstrated that utilization of a carrier such as hyaluronan or annular sealant significantly prevented cell leakage, and the rate of osteophyte formation resulting from cell leakage has been reported to be less than 2.7% in rabbit IVD model [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The storage modulus (G') of g-DAF-G was superior to that of DAF-G and increased with higher concentration of genipin (DAF-G: 465.51 Pa; 0.01 % genipin: 2.57 MPa; 0.02 % genipin: 3.29 MP; 0.04 %genipin: 4.34 MPa). Therefore, g-DAF-G showed improved biomechanical properties when compared to DAF-G (Peng et al, 2020).…”
Section: Injectable Strategies For Decellularised Matrix Administrationmentioning
confidence: 94%
“…However, other cell types and different repopulation methods have been widely investigated. As summarised in Table 3, successful recellularisation of IVD scaffolds [either injectable (Illien-Junger et al, 2016;Lin et al, 2016;Peng et al, 2020;Wachs et al, 2017;Xu et al, 2019;Yu et al, 2020;Zhou et al, 2018) or not] has already been reported with bovine and human (Illien-Junger et al, 2016;Wachs et al, 2017) NP cells as well as with rabbit (Liu et al, 2019) [either stem or not (Xu et al, 2014)] and human (Huang et al, 2016) AF cells.…”
Section: Recellularisation Of Decellularised Ivd Scaffoldsmentioning
confidence: 95%
See 2 more Smart Citations